Опорний конспект лекцій з дисципліни «Marketing Product Policy with the Commodity Science» для студентів денної форми навчання спеціальності 075 «Маркетинг» - Вишнівська, Богдана Вікторівна (My University, 2022)
The basic objectives of this course are to provide student with a broad introduction to marketing concepts, help to understand the factors that influence marketing decisions, and focus attention on the vital role of marketing in today’s global economy.
Рекомендовано науково-методичною радою факультету аграрного менеджменту НУБіП України
Keywords: Marketing Product Policy; Commodity Science